2011
DOI: 10.1113/jphysiol.2011.215988
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of junctin in the regulation of ryanodine receptors and calcium release in cardiac ventricular myocytes

Abstract: Junctin, a 26 kDa intra-sarcoplasmic reticulum (SR) protein, forms a quaternary complex with triadin, calsequestrin and the ryanodine receptor (RyR) at the junctional SR membrane. The physiological role for junctin in the luminal regulation of RyR Ca(2+) release remains unresolved, but it appears to be essential for proper cardiac function since ablation of junctin results in increased ventricular automaticity. Given that the junctin levels are severely reduced in human failing hearts, we performed an in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…Accordingly, previous studies showed that following high frequency electrical stimulation in the presence of isoproterenol, the JKO cardiomyocytes developed spontaneous Ca 2+ aftertransients and aftercontractions at significantly increased percentage, compared to WT cardiomyocytes. 12, 13 Using similar stress conditions, we demonstrated that 52% of the JKO cardiomyocytes present with spontaneous Ca 2+ aftertransients compared to only 10% of WT cells (p=0.0002). Preincubation of the JKO cardiomyocytes with KN-93 reduced in part and significantly (by 35%), the percentage of cells with Ca 2+ aftertransients (p=0.022) (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Accordingly, previous studies showed that following high frequency electrical stimulation in the presence of isoproterenol, the JKO cardiomyocytes developed spontaneous Ca 2+ aftertransients and aftercontractions at significantly increased percentage, compared to WT cardiomyocytes. 12, 13 Using similar stress conditions, we demonstrated that 52% of the JKO cardiomyocytes present with spontaneous Ca 2+ aftertransients compared to only 10% of WT cells (p=0.0002). Preincubation of the JKO cardiomyocytes with KN-93 reduced in part and significantly (by 35%), the percentage of cells with Ca 2+ aftertransients (p=0.022) (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Based on our biochemical data on RyR2 hyperphosphorylation and previous findings on increased SR Ca 2+ -leak in JKO cardiomyocytes 12, 13 , we proceeded to evaluate the effects of CaMKII inhibition on arrhythmogenesis, using isolated adult ventricular cardiomyocytes. One of the manifestations of arrhythmias associated with SR Ca 2+ leak at the cellular level is the appearance of spontaneous Ca 2+ aftertransients or arrhythmogenic Ca 2+ waves and aftercontractions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Refilling the SR Ca 2+ stores by SERCA during the recovery (restitution) phase once again increases luminal Ca 2+ , causing CASQ2 to dissociate from the RyR2s rendering these SR Ca 2+ release channels once more sensitized for yet another activation by cytosolic Ca 2+ . There is also evidence that has implicated other proteins such as TRD [56,58], JNT [59] and histidine-rich Ca 2+ binding protein [60] in regulation of RyR2. The potential role of these proteins in mediating the effects of luminal Ca 2+ on RyR2 function, as well as that of Ca 2+ -dependent CASQ2 polymerization-depolymerization as part of the luminal signaling cascade [35] requires further investigation.…”
Section: The Intermediary Luminal Ca2+ Sensormentioning
confidence: 99%